SURG-17. PROGNOSIS IN IDH-MUTANT GLIOMA: THE ROLE OF EXTENT-OF-RESECTION, AGE AND TUMOR GRADE. (14th November 2022) - van der Vaart, Thijs; van Garderen, Karin; Wijnenga, Maarten; Dubbink, Erik Jan; French, Pim; Smits, Marion; Dirven, Clemens M F; Kros, Johan; Vincent, Arnaud; van den Bent, Martin
Abstract: BACKGROUND: Evidence suggests that smaller residual tumor volumes after initial surgery are associated with longer survival in patients with astrocytoma, IDH-mutant, grade II. For IDH-mutant glioma of higher grade but also for oligodendroglioma, IDH-mutant, and 1p/19q codeleted, the impact of residual tumor volume on survival is unclear. This could be related to the limited follow-up of patients with oligodendroglioma that typically have long overall survival. We expanded a previously published series of patients increase the duration of follow-up and the spectrum of tumor grades. METHODS: Single center observational cohort study of patients with adult-type diffuse glioma, IDH-mutant, all WHO-2021 grades, from 2003 to 2021 . Molecular characteristics were assessed by next-generation targeted sequencing. Tumor volumes were calculated by semi-automatic 3D segmentation on pre- and postoperative MRI-scans. Associations between prognostic factors and survival were assessed using univariate and multivariate Cox proportional hazards models. RESULTS: 384 patients with IDH-mutant glioma (174 oligodendroglioma, 212 astrocytoma) were followed for a median of 7 years. Median age at diagnosis was 41 years (IQR 33 – 55). Significant prognostic factors for survival were Karnofsky performance status, 1p19q-status and post-operative tumor volume. Smaller post-operative tumor volume was associated with better survival, both in astrocytoma and oligodendroglioma. Age, tumor grade and MRI-contrast enhancement were not associated with survival. CONCLUSION: Lower residual tumor volume after first surgery is a strong prognostic factor in all IDH-mutant glioma subgroups, even in patients with very small residual tumor. Importantly, age and histological tumor grade were not significantly associated with survival. The data serves as further support for optimal initial resections of tumors suspected for IDH-mutant glioma, also in oligodendroglioma.